The ten harmful myths of psychiatry - Slade, Mike (Journal of Recovery in Mental Health)

(untitled) (Ontario Shores Centre for Mental Health Sciences, 2025)
Psychiatry has powerfully influenced how mental health issues are conceptualised and addressed internationally. Many people report benefits from mental health assessment and treatment, but other individuals report being harmed by the mental health system. In this regard, mental health services are distinct from other areas of health care. For example, no other area of medicine has an equivalent of a psychiatric survivor movement. This article identifies ten embedded assumptions within psychiatry, which may account for some of these negative experiences. They are myths, in the sense of being beliefs which are widely held, often un-noticed and un-challenged, and routinely applied as if universally true despite being either wholly untrue or only sometimes true. They are also harmful, both in creating direct damage and in consuming patient, clinician, and societal resources which could be better spent in other ways. The myths are: Mental health problems are individual; Mental ill-health is fundamentally biological; A clinician knows what is in the patient’s best interests; A clinician can predict the patient’s future; Diagnosis is fact; Treatment is always justified; Patients need to be trained for social roles; Side effects are peripheral; Improvement is always due to treatment; and Supporting recovery is ‘business as usual’. Approaches to developing new knowledge about mental health are then proposed: learning from people living with mental health issues and not using services; developing a salutogenic knowledge base about wellness to balance our current pathogenic knowledge base about illness; and using standpoint epistemologies to develop more inclusive approaches to knowledge creation.